Ethnomedicinal and traditional application of Allium wallichii Kunth (Himalayan Onion): An unexplored and underutilized nutraceutical plant foods from Himalayan regions. - Rana, Vijay Singh; Sethiya, Neeraj; Duseja, Manisha; Gupta, Rupa; Bisht, Dheeraj; Gangal, Avinash (Ethnobotany Research and Applications, 2022)
Background: Allium wallichii Kunth (Family: Amaryllidaceae), commonly known as “Himalayan onion” is well recorded as popular ethnomedicine for medicinal and nutritional uses by different people and communities native to Bhutan, India, Myanmar, Nepal and Southwestern China. Methods: Despite the wide ethnomedicinal and pharmacological studies on A. wallichii, there are no concise elaborated article comprising reviews of published literature. So, herein we designed this review article to discuss the potential health benefit in both traditional ethnopharmacology and modern pharmacology. To achieve this exhaustive literature searches using A. wallichii as keywords for screening of relevant information online databases such as Google Scholar, PubMed, Science Direct, SciELO, Scopus and SpringerLink were performed. Results: Only few published studies relevant to our objective was found and presented under different section of the current work. It was observed that different parts of A. wallichii was recorded in different regions of the Asia for health, economical and nutraceutical benefits such as dysentery, cholera, cold, cough, blood cholesterol levels, itching, to remove maggots from wounds, leech remover, antidote, cut, wounds (finger and toe infections), gastric problems, bile complaints, moth repellent, bodyache, sinusitis, carminative, dizziness, mumps, hypertension, intestinal pain, liver diseases, indigestion for children, high altitude sickness, condiment for curries, pickles, soup and vegetable source for cash income. Major bioactive phytochemicals such as 1,2 bis (methylthio) ethene, diosgenin, 2,4 dimethyl thiophene, tigogenin, dimethyl disulfide and trisulfide were reported. However, in modern pharmacology anti-microbial, antioxidant, and anti-cancer activities was established. Conclusion: It was concluded that A. wallichii need special attention for protected cultivation and conservation in near future for maximum output and utilization are required. Moreover, A. wallichii could be considered as an excellent source of safe and effective medicinal and nutritional herbal remedies for human and animal consumption after only careful investigation. Keywords: Allium wallichii, Himalayan onion, Nutraceuticals, Anti-cancer